Theory of mind profile and cerebellar alterations in remitted bipolar disorder 1 and 2: a comparison study - Olivito, Giusy; Lupo, Michela; Siciliano, Libera; Gragnani, Andrea; Saettoni, Marco; Pancheri, Corinna; Panfili, Matteo; Pignatelli, Fabiana; Delle Chiaie, Roberto; Leggio, Maria (Frontiers in Behavioral Neuroscience, 2022)
The literature on social cognition abilities in bipolar disorder (BD) is controversial about the occurrence of theory of mind (ToM) alterations. In addition to other cerebral structures, such as the frontal and limbic areas, the processing of socially relevant stimuli has also been attributed to the cerebellum, which has been demonstrated to be involved in the abovementioned disorder. Nevertheless, the cerebellar contribution to ToM deficits in bipolar patients needs to be elucidated further. To this aim, two tests assessing different components of ToM were used to evaluate the ability to appreciate affective and mental states of others in 17 individuals with a diagnosis of BD type 1 (BD1) and 13 with BD type 2 (BD2), both in the euthymic phase, compared to healthy matched controls. Cerebellar grey matter (GM) volumes were extracted and compared between BD1 and controls and BD2 and controls by using voxel-based morphometry. The results showed that BD1 patients were compromised in the cognitive and advanced components of ToM, while the BD2 ToM profile resulted in a more widespread compromise, also involving affective and automatic components. Both overlapping and differing areas of cerebellar GM reduction were found. The two groups of patients presented a pattern of GM reduction in cerebellar portions that are known to be involved in the affective and social domains, such as the vermis and Crus I and Crus II. Interestingly, in both BD1 and BD2, positive correlations were detected between lower ToM scores and decreased volumes in the cerebellum. Overall, BD2 patients showed a more compromised ToM profile and greater cerebellar impairment than BD1 patients. The different pattern of structural abnormalities may account for the different ToM performances evidenced, thus leading to divergent profiles between BD1 and BD2.